Determinants of economic growth : a cross-country empirical study - Barro, Robert J. (Cambridge, Mass. : The MIT, 1997)
Hundreds of empirical studies on economic growth across countries have highlighted the correlation between growth and a variety of variables. Determinants of Economic Growth, based on Robert Barro's Lionel Robbins Memorial Lectures, delivered at the London School of Economics in February 1996, summarizes this important literature.
The book contains three essays. The first is a survey of the research on the determinants of long-term growth through the estimation of panels of cross-country data. The second essay details the interplay between growth and political freedom or democracy and finds some evidence of a nonlinear relationship. At low levels of political rights, an expansion of rights stimulates growth; however, once a moderate level of democracy has been obtained, a further expansion of rights reduces growth. The final essay looks at the connection between inflation and economic growth. Its basic finding is that higher inflation goes along with a lower rate of economic growth.
Includes bibliographical references p. 131-139 and index.
Keywords: Economic development -- Cross-cultural studies; Economic policy -- Cross-cultural studies